2009
DOI: 10.1093/brain/awp186
|View full text |Cite
|
Sign up to set email alerts
|

Reality of auditory verbal hallucinations

Abstract: Distortion of the sense of reality, actualized in delusions and hallucinations, is the key feature of psychosis but the underlying neuronal correlates remain largely unknown. We studied 11 highly functioning subjects with schizophrenia or schizoaffective disorder while they rated the reality of auditory verbal hallucinations (AVH) during functional magnetic resonance imaging (fMRI). The subjective reality of AVH correlated strongly and specifically with the hallucination-related activation strength of the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 50 publications
6
67
1
1
Order By: Relevance
“…The task-related power changes in both hemispheres were negatively correlated and the task-related coherence differences in the right hemisphere were positively correlated with the hallucination score in schizophrenic patients. The cerebral areas we identified were in line with those reported previously in studies observing an involvement of frontal [55,56] and temporal [55,57] areas in schizophrenia with auditory hallucinations.…”
Section: Discussionsupporting
confidence: 90%
“…The task-related power changes in both hemispheres were negatively correlated and the task-related coherence differences in the right hemisphere were positively correlated with the hallucination score in schizophrenic patients. The cerebral areas we identified were in line with those reported previously in studies observing an involvement of frontal [55,56] and temporal [55,57] areas in schizophrenia with auditory hallucinations.…”
Section: Discussionsupporting
confidence: 90%
“…Abnormal activation of right hemisphere regions is a frequently reported finding in patients who have AVHs, where activation changes have been most consistently reported for areas of the prefrontal and temporal cortices. 45,55,59 These findings have been discussed within the context of a disrupted language lateralization in patients who have AVHs. 2,60 The data provided by our study, however, suggest the involvement of an RSN distinct from the network subserving language.…”
Section: Discussionmentioning
confidence: 97%
“…10,11 This hypothesis has been supported by the results of imaging studies, which have found increased metabolism of the vStr during positive symptoms 12 and have correlated NAcc activation to the vividness of hallucinations. 13 Moreover, several authors have proposed that DAergic transmission may indirectly contribute to hallucinations by inducing aberrant salience processes, impairing sensory integration. 14 Nevertheless, the extent to which the mesolimbic pathway is involved in the pathophysiology of hallucinations and depends on the elicited sensory modalities remains unclear.…”
Section: Introductionmentioning
confidence: 99%